Integration of Prophetic Paradigms Into Higher Education System - M. Fajru Sidqi (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Character education is a basic need to answer the moral decadence and integrity of educated people. Integrity is also a basic asset for tertiary education graduates in their service. It is not surprising if educated people must have good cognitive abilities. They need to be equipped with a vision of life in the form of service. So that even in the world of work they can adjust well. The government has arranged KKNI as a standardization of graduates for cognitive, psychomotor and affective abilities that must be met. As a formal legal basis, KKNI needs to be approached with a clear scientific model. Prophetic science can be an answer to translate the KKNI concept into higher education learning. The prophetic education paradigm of Heddy Shri Ahimsa Putra teaches that humans basically have two functions of the ethos of devotion, namely devotion to God Almighty, and devotion to humanity. With the integration of prophetic scholarship into KKNI, there will be no demarcation and scientific dichotomy on religious beliefs because all learning and work processes, their orientation will end in service